2012
DOI: 10.1016/j.rbmo.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Semen donors who are open to contact with their offspring: issues and implications for them and their families

Abstract: This study investigates the motivations, views and experiences of semen donors willing to have contact with their offspring. An online questionnaire for semen donors was posted by the US-based Donor Sibling Registry in 2009. A total of 164 respondents who had previously been donors completed the questionnaire, which consisted of 45 open and closed questions covering motivations for donating, health and medical information, experiences of donating, contact with offspring and implications of donating and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 25 publications
4
63
0
3
Order By: Relevance
“…Because the majority of donors in the present study were in a relationship and a considerable percentage of donors had moved on to a new partner since the donation, this can be also seen as a potential challenge here. Being a donor is not solely an individual contribution to giving a couple the opportunity to become parents because it may also lead to a wider constellation of relationships extended beyond the donor and the donation offspring, something that also has been highlighted in previous research (17). Donors reported different preferences regarding receiving information when an offspring requests identifying information about them.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because the majority of donors in the present study were in a relationship and a considerable percentage of donors had moved on to a new partner since the donation, this can be also seen as a potential challenge here. Being a donor is not solely an individual contribution to giving a couple the opportunity to become parents because it may also lead to a wider constellation of relationships extended beyond the donor and the donation offspring, something that also has been highlighted in previous research (17). Donors reported different preferences regarding receiving information when an offspring requests identifying information about them.…”
Section: Discussionmentioning
confidence: 92%
“…Jadva et al (16) reported on positive experiences from meetings between the donors and the offspring, which is comforting. However, Daniels (17) revealed that the major challenge in contact between donor and offspring was the contact and relationship with the donor's own family. Because the majority of donors in the present study were in a relationship and a considerable percentage of donors had moved on to a new partner since the donation, this can be also seen as a potential challenge here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the experiences of donors has started to be undertaken and indicates that some semen donors continue to have thoughts and feelings that arise from their having been a donor. These include retaining an interest in those to whom they are genetically related regardless of any social contact (Crawshaw et al, 2007, Jadva et al, 2011, Daniels et al, 2012. As with the recipients ' views in this study, the meanings and experiences of donors associated with semen donation are dynamic -in other words they continue to develop and may change following donation in line with philosophical beliefs and personal and social experiences of the recipients (Daniels et al, 2005;Crawshaw et al, 2007).…”
Section: Research and Clinical Implicationsmentioning
confidence: 85%
“…Pour certains de ces hommes, le don de sperme représen-te une façon d'avoir des enfants, mais sans en avoir réellement (Almeling, 2011;Côté, 2012Côté, , 2014Daniels et al, 2012). Riggs (2008) parle alors d'un «désir d'immortalité génétique» plutôt que d'un désir de paternité.…”
Section: Introductionunclassified